2018
DOI: 10.1021/acs.jafc.8b01726
|View full text |Cite
|
Sign up to set email alerts
|

Potato Peels and Their Bioactive Glycoalkaloids and Phenolic Compounds Inhibit the Growth of Pathogenic Trichomonads

Abstract: Potato peel, a waste product of the potato processing industry, is high in bioactive compounds. We investigated the in vitro antitrichomonad activity of potato peel powders prepared from commercial Russet, red, purple, and fingerling varieties as well as several known potato components, alkaloids and phenolic compounds, against three pathogenic strains of trichomonads. Trichomonas vaginalis is a sexually transmitted protozoan parasite that causes the human disease trichomoniasis. Two distinct strains of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 29 publications
(41 reference statements)
2
26
1
Order By: Relevance
“…In a recent study, Friedman et al reported that the GAs α-chaconine and α-solanine were highly active against three pathogenic strains of trichomonads. These authors also reported that the activity of α-solanine was several times higher than α-chaconine; which is contrary to the several previous results where the influence of α-chaconine was reported higher than that of α-solanine [105]. Several other research works regarding the impact of potato glycoalkaloids on the membrane of frog embryos [106][107][108] and on fungi such as A. crenulatus, A. brassicicola, P. medicaginis, and R. solani [109,110] showed that α-chaconine was more active than α-solanine.…”
Section: Antifungal Antimicrobial and Insecticidal Activitycontrasting
confidence: 76%
“…In a recent study, Friedman et al reported that the GAs α-chaconine and α-solanine were highly active against three pathogenic strains of trichomonads. These authors also reported that the activity of α-solanine was several times higher than α-chaconine; which is contrary to the several previous results where the influence of α-chaconine was reported higher than that of α-solanine [105]. Several other research works regarding the impact of potato glycoalkaloids on the membrane of frog embryos [106][107][108] and on fungi such as A. crenulatus, A. brassicicola, P. medicaginis, and R. solani [109,110] showed that α-chaconine was more active than α-solanine.…”
Section: Antifungal Antimicrobial and Insecticidal Activitycontrasting
confidence: 76%
“…These results suggest that the difference in SGA content between the light exposure and control groups originated from the skins, namely, light affected SGA accumulation in the skin and not in the flesh, for which further molecular and genetic evidence is required to elucidate the mechanism. The potential use of the tuber peels for targeted therapeutic treatments against pathogenic parasite such as trichomonads should be taken into account due to tuber peels are rich in bioactive compounds SGA (Friedman et al, 2018).…”
Section: Sga Content Of Potato Tuber Across All Experimental Sessionsmentioning
confidence: 99%
“…Beside their toxicity and detrimental effects, numerous studies investigated the beneficial biological properties of glycoalkaloids such as antibiotic activities against bacteria, fungi, viruses and protozoa (Niño et al ., ; Friedman et al ., ; Lelario et al ., ). Additionally, numerous studies reported pharmaceutical activities of glycoalkaloids against many diseases and metabolic disorders such as inflammation, glycemia, allergies, fever and even certain types of cancers (Camire et al ., ; Patel et al ., ; Liu et al ., ; Friedman, ).…”
Section: Introductionmentioning
confidence: 98%